Supply electrically operated sick / disabled vehicles of category 18 of the aids register under [section] 139 sgbv. [Tender documents : T27659733] (MENA Report, 2015)
Subject of the tender is the establishment of a framework agreement with one company per lot to supply the miners insured with electrically operated hospital / invalid carriages including all services and services related therewith associated in accordance with the terms of reference. The contract is divided into 28 regional lots. The Loszuschnitt with specific zip codes can be called with the short link www.kbs.de/ausschreibung-eu-weit (Appendix 4 - Gebietslosaufteilung by postal code of the tender documents) .